Analisis Strategi Personal Branding Agus Astika (Akustika Enterprise) Di Instagram Dan Youtube - Almanto, Reymond (Peneliti.net, 2023)
The music industry is growing rapidly, but many musicians face difficulties in promoting themselves and their skills, especially amid the pandemic. Many music events have been postponed or canceled, resulting in an overall decline in income. For musicians who are paid based on projects and have a limited understanding of marketing strategies, this situation becomes very challenging. Agus Astika, the founder of Akustika Enterprise, is a successful musician who provides top-tier musician/band services in Bali. This research aims to analyze Agus Astika's personal branding strategies on Instagram and YouTube, the reasons for choosing these platforms as the venue for designing strategies, also the implications of soft skills on client loyalty and demand for services from Akustika Enterprise as a musician. This research combines qualitative and quantitative data to analyze Agus Astika's personal branding (Akustika Enterprise). The study draws on personal branding theories from Montoya dan Rampersad, digital marketing from Beridze & Mamuladze, and sociology of art concepts, focusing on soft skills from Andriyadi, Attitudes and Behaviors by Sarlito and Eko, and Art Entrepreneurship by Scherdin and Zander. Data is collected from human informants and non-human sources, with informants serving as key subjects providing valuable soft data. Qualitative data sources include documents, images, and other relevant materials. Data collection methods involve observation, in-depth interviews, literature review, and documentation following Bogdan & Biklen's approach. The data is then analyzed using Miles & Huberman's methodology, including data collection, reduction, presentation, and verification. The research findings indicate that Agus Astika (Akustika Enterprise) has fulfilled six out of eight characteristics of personal branding according to Montoya, as well as eight out of eleven characteristics according to Rampersad. Akustika Enterprise targets potential clients through Instagram, one of the most popular social media platforms, and utilizes YouTube as a showcase for their work. Possessing strong soft skills offers various benefits, including enhancing brand image, fostering client loyalty, and building relationships with potential clients.